What is the effect of the early follicular phase FSH/LH ratio on the number of mature oocytes and embryo development? - Arat, Ozgur; Deveci, Derya; Ozkan, Zehra Sema; Tuncer Can, Sevim (Tubitak Scientific & Technological Research Council Turkey, 2020)
Background/aim: Basal level of follicle stimulating hormone (FSH), luteinizing le (LH), estradiol (E2), and antral follicle count are used as predictors of ovarian reserve before starting ovulation induction. e aimed to investigate the predictor potential of early fbllictilar phase FSH/LH ratio on controlled ovarian hyperstimulation-intrac Aasmic sperm injection (COH-ICSI) cycle outcomes. Materials and methods: This retrospective cohort study was conducted with 648 COH-ICSI cycles pertbrmed between 2012 and 2014. Cycles were classified according to their basal FSH/LH ratio, group 1(01) = FSH/LH ratio < 2, N = 473 and group 2(G2) = FSH/LH ratio 2, N = 175. Demographic characteristics and stimulation parameters were evaluated. Retrieved total oocyte count (TO C), mature oocyte count (MOO, transferred embryo number, and pregnancy results were obtained and transferred to computer by SPSS 21.0 programme. Results: TOC and \1O( of G1 were signilieantly higher than those of '2 l he total gonadotrophin doses of 02 were significantly higher than 0l. I here was no significant difference between groups for transferred embryo number. Pregnancy and live birth rates were similar in both groups. Conclusion. In our population, increased FSH/LH ratio did not affect he rates of pregnancy and live birth negatively.
Keywords: FSH/LH ratio; attire oocyte; pregnancy rate; live birth rate